Dynamic Performance of Trams Based on Grooved Track - Yang YANG; Fu LI; Jincheng LI; Junjun DING (机车电传动)
The dynamic models of 70% low-floor trams using groove track and non-groove track were established respectively. Several aspects were discussed including analysis of the condition which occurs flange contact, exploring flange contact effects on dynamic of groove track, optimizing the distance of rolling tread circle. The results of the dynamic performance of trams based on groove rail showed that: flange contact is very unfavorable to wheel alignment, so it is necessary to ensure that the wheel is not in contact with the groove track in vehicle design; increasing the distance of rolling tread circle is a quick way to avoid the flange contact and proper increasing the distance of rolling tread circle is beneficial to vehicle dynamic property.